Comparison on the factors that influence consumers’ preference between wet market and modern market / Farhana Ab. Aziz and Nadwatu Najihah Abdul Manap - Ab. Aziz, Farhana; Abdul Manap, Nadwatu Najihah (2019)
The main study of this undergraduate project is to investigate the factors that influence consumers’ preference toward wet market and modern market. This study was done by using secondary studies which are argumentative and comparative analysis. The comparative analysis is done between the wet market and modem market. The factors that influence consumers’ preference are quality of product, product packaging, store atmosphere and product pricing. Quality of product refers to the freshness, safety, color, taste, odor and value. The perception on the product quality towards each retail format is apparently different from each customer. Besides, modem retailers provide packaged product that certain customers would rather choose because they assumed that packaged product would have better quality compared to fresh product sold at the wet markets. Younger customers prefer packaged product with halal logo. The store atmosphere in wet market was labeled as crowded, hot, stuffy and dirty while modem market is clean and it provide enough parking spaces for the consumers. The facilities and layout design of modem market is better than wet market. As for product pricing, wet market offers cheaper price compared to modem market which is higher and fixed price. From the discussion, consumers prefer going to the wet market because they want to purchase fresh product such as fruits and vegetables, meat, poultry and seafood. As for modem market, they would like to purchase item such as clothes, pants, packed product or convenience food and dry product.